2008
DOI: 10.1163/156854108785787299
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular analysis of six aphelenchoidoids from Australian conifers and their relationship to Bursaphelenchus (Fuchs, 1937)

Abstract: Six isolates of Australian Aphelenchoidoidea, viz., Laimaphelenchus preissii from native coniferous Callitris preissii trees, L. australis from the common pine plantation trees of Pinus radiata and P. pinaster and L. heidelbergi and two morphospecies of Aphelenchoides (H1 and K1) and Cryptaphelenchus sp. (K2) from diseased P. radiata trees, were studied using light microscopy, scanning electron microscopy and phylogenetic analyses of nearly full length sequences of SSU, D2/D3 expansion segments of LSU rDNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 14 publications
5
22
0
Order By: Relevance
“…is grouped with other genera of Aphelenchoidinae, i.e., Ficophagus Davies, Ye, Kanzaki, Bartholomaeus, Zeng, and Giblin-Davis, 2015, Martininema Davies, Ye, Kanzaki, Bartholomaeus, Zeng, and Giblin-Davis, 2015, Laimaphelenchus Fuchs, 1937, and Schistonchus s.s. Davies, Ye, Kanzaki, Bartholomaeus, Zeng, and Giblin-Davis, 2015, in clade 2. According to our molecular analysis, the members of the genus Aphelenchoides appears to be paraphyletic, a finding that agrees with previous studies (Zhao et al, 2008;Rybarczyk-Mydl À owska et al, 2012;Wang et al, 2013;Fang et al, 2014aFang et al, , 2014bMiraeiz et al, 2015;Esmaeili et al, 2016aEsmaeili et al, , 2016bGolhasan et al, 2016). Furthermore Aphelenchoides, Laimaphelenchus, and Schistonchus s. l cannot be clearly separated, possibly implying that all the genera share a recent common ancestor (Zeng et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…is grouped with other genera of Aphelenchoidinae, i.e., Ficophagus Davies, Ye, Kanzaki, Bartholomaeus, Zeng, and Giblin-Davis, 2015, Martininema Davies, Ye, Kanzaki, Bartholomaeus, Zeng, and Giblin-Davis, 2015, Laimaphelenchus Fuchs, 1937, and Schistonchus s.s. Davies, Ye, Kanzaki, Bartholomaeus, Zeng, and Giblin-Davis, 2015, in clade 2. According to our molecular analysis, the members of the genus Aphelenchoides appears to be paraphyletic, a finding that agrees with previous studies (Zhao et al, 2008;Rybarczyk-Mydl À owska et al, 2012;Wang et al, 2013;Fang et al, 2014aFang et al, , 2014bMiraeiz et al, 2015;Esmaeili et al, 2016aEsmaeili et al, , 2016bGolhasan et al, 2016). Furthermore Aphelenchoides, Laimaphelenchus, and Schistonchus s. l cannot be clearly separated, possibly implying that all the genera share a recent common ancestor (Zeng et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Small subunit of rDNA contains sufficient phylogenetic signal for the identification of Aphelenchoides species (De Ley et al, 2006;Zhao et al, 2008;Van Megen et al, 2009) and have been shown to be more useful for species identification compared to D2-D3 expansion segments of 28S rRNA and internal transcribed spacer rRNA, as both of these markers showed more species variability than did partial 18S rDNA (Zhao et al 2008;Esmaeili et al, 2016). This is the second new species of the genus from Iran to be described and sequenced.…”
Section: Discussionmentioning
confidence: 95%
“…In a study of Laimaphelenchus and Aphelenchoides species, Zhao et al (2008) showed that i) L. preissii and Aphelenchoides sp. (EU287599) were a sister group ii) L. heidelbergi and Aphelenchoides sp.…”
Section: Molecular Characterisationmentioning
confidence: 99%